Terapi Al-Qur’an untuk Menyembuhkan Penyakit: : Studi Living Qur’an dan Hadis Berdasarkan Pendekatan Fenomenologi Edmund Husserl - Muttaqin, Khairul; Badri Amien, Ach; Wulandari, Suci (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
Nowadays, there are several alternative treatments undertook by certain practitioners to cure a person's illness. The diseases they treat are physical or non-physical. Physical disease is a disease that can be identified by medical science, while non-physical disease cannot be identified by medical science, it is called a non-medical disease. Physical ailments are examined and prescribed by doctors or other health professionals to relieve or cure the ailments. On the other hand, non-physical ailments are given alternative treatments such as prayer or certain herbs. The problems investigated in this study are as follows. First, the phenomenon of Quranic therapy to cure physical and non-physical ailments in Sumenep. Second, the meaning of Quranic therapy to cure physical and non-physical diseases in Sumenep. Third, the view of phenomenological theory on Quranic therapy to cure physical and non-physical diseases in Sumenep. The phenomenological approach is used to analyze data about Quranic therapy to cure physical and non-physical ailments. The meaning or essence behind the phenomenon is analyzed by releasing the surrounding empirical data and situation. The results of this study are, first: Surah Muhammad is often used for the treatment of ailments by the Sumenep Pragaan community. Sick people are recited the surah in the hope that their illness will be cured. The reading of Surah Muhammad for treatment is sometimes collaborated with readings other than the Qur'an such as burdah, ratibul haddad, or shalawat nariyah. In addition to the tradition of reciting Surah Muhammad, there is also a ruqyah tradition for treatment. Ruqyah is the practice of Al-Qur'an therapy carried out by Jam'iyah Ahl al-Ruqyah Aswaja (JRA) Sumenep to treat physical and non-physical ailments suffered by people in Sumenep Regency. Ruqyah therapists recite selected verses in performing Quranic therapy. Second, the meaning of reciting the verses of the Quran for medical treatment or non-medical therapy is actually an intermediary. In other words, healing is not determined by these readings. Third, the final stage of Husserl's phenomenological analysis is transcendental reduction, understanding phenomena by tracing the roots in the consciousness that manifests itself so that pure existence or subjects can be found. The pure existence or subject of reciting surah Muhammad, Surah al-Falak, and other verses in the practice of ruqyah is the awareness that all these things are done for the sake of expecting the blessing of Allah SWT.